Traumatic Dental Injuries Among 6 – 13 – Year - Old - School Children in Tikrit City (Mustansiria Dental Journal, 2024)
Background: An injury to both primary and permanent teeth and the supportingstructures is one of the most common dental problems seen in children. The extentof injury may vary from mild chipping of enamel to sever maxillofacial injury.The aim of this study was to find out the prevalence of traumatized anterior teethamong primary school children.Materials and methods: This study is a cross-sectional survey was carried outthrough clinical examination of anterior teeth among 720, 6-13 year old childrenenrolled in primary public schools of tikrit city. The prevalence of traumatizedanterior teeth was studied in relation to age, gender, type of injury in addition tothe cause of fracture. Recording and diagnosis of dental fracture were assessedaccording to Garcia-Godoy classification.Results: Males were more affected than females with odds ratio was 2.53 andstatistically was significant. The higher prevalence of dental trauma was recordedamong the age 10-11 year old. The permanent maxillary central incisors were themost frequent injured tooth and the most frequent type of fracture was the Class IIEnamel-Dentine, fracture without pulp exposure. Fall and playing were the mostfrequent causes of dental injury.Conclusion: data of the present study clearly show the need for dental healtheducation of children and their parents, so prevention programs are needed toimprove the dental health of Iraqi children.